2009
DOI: 10.1007/s11239-009-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, pharmacokinetics and pharmacodynamics of the factor Xa inhibitor apixaban in rabbits

Abstract: Apixaban has similar affinity for human and rabbit factor Xa (FXa). Rabbits are commonly used in development of thrombosis disease models; however, unlike in other species, apixaban demonstrated poor oral bioavailability (F = 3%) and a high clearance rate (2.55 l/h/kg) in rabbits. Oxidative metabolism of [14C] apixaban by liver microsomes was approximately 20 times faster in rabbits than in rats or humans. Following an intravenous (IV) dose of 5 mg/kg, circulating levels of [14C] apixaban decreased from the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Administration of apixaban was associated with a fast onset of action and concentration-dependent increases in plasma anti-Xa activity, consistent with the expected effects of a direct factor Xa inhibitor 12,24. As observed in previous studies, the time course of anti-Xa activity closely tracked the apixaban plasma concentration–time profile, with a direct linear relationship between the two that exhibited no temporal lag 12,25.…”
Section: Discussionsupporting
confidence: 85%
“…Administration of apixaban was associated with a fast onset of action and concentration-dependent increases in plasma anti-Xa activity, consistent with the expected effects of a direct factor Xa inhibitor 12,24. As observed in previous studies, the time course of anti-Xa activity closely tracked the apixaban plasma concentration–time profile, with a direct linear relationship between the two that exhibited no temporal lag 12,25.…”
Section: Discussionsupporting
confidence: 85%
“…Addition of 3Ј-phosphoadenosine 5Ј-phosphosulfate, the sulfation cofactor, and human liver cytosol to the HLM incubations did not change the rate or profile of apixaban metabolism. Apixaban was also metabolized by HLM isolated from young donors, and the metabolite formation profiles were qualitatively similar to those for HLM from adults (Table 1) and comparison with previously identified metabolites in animals and humans (Zhang et al, , 2010, these three metabolites were identified as O-demethyl apixaban (M2) and two hydroxylated apixaban derivatives (M4 and M7).…”
Section: [ 14 C]apixaban Metabolism In Hlm Incubations Biotransformasupporting
confidence: 72%
“…Apixaban is efficacious and well tolerated in the treatment of patients with acute symptomatic deep vein thrombosis (Buller et al, 2008). After oral administration, apixaban was slowly metabolized and thus was mostly unchanged in the circulation although apixaban was metabolized by multiple pathways in animals and humans (Zhang et al, , 2010. The primary metabolic pathways of apixaban in humans included O-demethylation (M2) and hydroxylation (M4 and M7).…”
Section: Apixaban (mentioning
confidence: 99%
“…Furthermore, rabbit models have been found to be suitable models for assessment of FXa inhibitors. This is because they are comparable to humans in terms of in vitro anticoagulation effect of FXa inhibitors [43], and are more sensitive to small molecule FXa inhibitors than mice, rats or dogs [44,45]. In addition, the use of a randomised design and of both placebo and negative control groups allowed for a rigorous evaluation of rivaroxaban reversal with 4F-PCC.…”
Section: Discussionmentioning
confidence: 99%